A Green Approach to Collect Income Taxes to Save the Nature - Ramu, Sridarala; Venkateshwar Reddy, Kasireddy; Pal singh, Surinder; Krishnaveni, Birudaraju; Madhusudan, Patlola; Divya vani, Busakari (International Journal of Psychosocial Rehabilitation, 2020)
Money and technology cannot save the nature;; only pro-environmental behavior [1] of society can save the nature. Energy consumption is an index of the financial status of a society. Financially rich societies consume more energy than poorer societies. Example: advanced nations like the USA and Canada occupy about 5% of the world population but utilize one-fourth of global energy. An average individual there utilizes 300 GJ in a year. But an average person in poor nations like Bhutan, Nepal, or Ethiopia utilizes less than 1 GJ per year. So the amount of energy utilized by a person in a rich country in one day is almost equal to the amount of energy utilized by a person in a poor country in a whole year. It indicates that financially rich societies and nations consume more energy [2].